Expression and prognostic value of estrogen-related receptor β alternative splicing isoforms in esophageal squamous cell carcinoma - Kai-Yuan Jiang; Jia-Xin Wan; Hong-Yun Li; Wei-Yang Chen; Chun-Mei Shen; Ke-Xuan Guo; Xiang-Yun Zheng; Hong-Ying Wen; Dong Tian (European Journal of Medical Research)
Abstract Background Estrogen-related receptor β (ERRβ) alternative splicing isoforms, including ERRβsf, ERRβ2, and ERRβΔ10, have been implicated in the pathogenesis of malignant tumors. Nevertheless, their specific impact on esophageal squamous cell carcinoma (ESCC) remains unclear. The study aimed to investigate the expression and prognostic value of ERRβ alternative splicing isoforms in ESCC. Methods This study prospectively collected ESCC tissues and paired normal tissues of 54 patients with ESCC who underwent esophagectomy without neoadjuvant therapy. The protein expression levels of ERRβ alternative splicing isoforms in ESCC and normal tissues were detected by Western blot. The Kaplan–Meier method with a log-rank test was used to estimate overall survival (OS). The Cox proportional hazards regression analysis was used to evaluate the independent prognostic factors. Results In ESCC tissues, the ERRβsf/ERRβ ratio was significantly higher (P = 0.017) compared to paired normal tissues. Based on a cut-off value of 0.24, there were 18 and 36 cases in the high ERRβsf/ERRβ expression group and low ERRβsf/ERRβ expression group, respectively. Patients with high ERRβsf/ERRβ ratios had significantly better OS than those patients with low ERRβsf/ERRβ ratios (77.1% vs 50.8%, P = 0.024). The multivariate analysis revealed that ERRβsf/ERRβ (hazard ratio [HR] = 0.219, 95% confidence interval [CI] 0.063–0.767, P = 0.018) and N stage (HR = 7.892, 95% CI 1.328–46.911, P = 0.023) were independent prognostic factors for ESCC patients. Conclusions This study is the first to demonstrate the relationship between ERRβ alternative splicing isoforms in ESCC. A high ERRβsf/ERRβ ratio was associated with a better prognosis, indicating that ERRβ alternative splicing isoforms may serve as potential prognostic biomarkers for ESCC.